Michigan Mute Swan Management: A Case Study to Understand Contentious Natural Resource Management Issues. Issue 3 (3rd May 2016) - Jager, Corey; Nelson, Michael Paul; Goralnik, Lissy; Gore, Meredith L.
ABSTRACT: U.S. state fish and wildlife agencies have responded to perceived ecological and social threats posed by mute swans by implementing population control strategies. In Michigan, some stakeholder groups have vocally opposed particular control activities. To better understand and characterize key aspects of the underlying media dialogue about mute swan management in Michigan, one factor in the development of public perceptions about wildlife issues, we conducted a qualitative content analysis of Michigan-specific online news articles. Results revealed tensions between stakeholder groups about management priorities were rooted in differing ideas about healthy social and ecological systems, appropriate wildlife behavior, and the acceptability of lethal control (i.e., shooting living birds). Characterizing which stakeholder groups aligned with particular arguments might allow managers to tailor and direct messaging to specific audiences.